An evaluation of critical success factors in oil and gas project portfolio in Nigeria - Fiberesima , Damiebi Denni-; Abdul Rani, Nazatul Shimax (Advances in Aquaculture and Fisheries Management, 2020)
This study focuses on investigation of the critical success factors required for successful deepwater development in offshore Nigeria. Thirteen critical success factors were established along with project delivery schedule, project budget and portfolio management strategy as impacting on project success. A sample of 200 participants were identified and issued with a set of self developed items web based questionnaire, with the variable items drawn from the literature review. 85% of the target sample responded to the electronic mail web based questionnaire. The findings of this research show that, thirteen critical success factors are of high importance within the deepwater oil and gas project portfolio management. It also identified that some critical success factors in mega construction projects can be applied to deepwater oil and gas projects